Pure Bending Characterization of Nb3Sn Superconducting Strands Using Experimentation and FEA Modeling. - Allen, Nathaniel. (2017)
Abstract: Superconductors are important technological materials for developing high field magnets. Nb3Sn is a particularly common superconducting material for these magnets because of its high current and field capabilities. However, Nb3Sn is also very sensitive to strain which can degrade its electrical performance. For this reason, the strain-dependent behavior of Nb3Sn has been an important research topic for many decades. This thesis focuses on characterizing the strain-dependent behavior of Nb3Sn strands under pure bending loads. This work is the continuation of pure bending research that started in 2005 at the MIT. A discrepancy in the critical current results of two different sample holders at the same amount of applied bending was observed in prior pure bending experiments conducted in 2012. The unknown cause behind this discrepancy led to the focus and motivation behind the current pure bending research. An in-depth FEA investigation of the samples holders was undertaken to identify a potential cause for the observed difference in experimental critical current results. The FEA modeling focused on characterizing the strain distributions within the Nb3Sn strands mounted on the sample holders. A comparison between the critical current results and the strain distributions from each sample holder uncovered an adverse characteristic which may have caused the discrepancy. Following these findings improved sample holders were designed to eliminate this adverse characteristic. The performance of the newly developed sample holders were then validated through experiments. Both bronze-route and internal-tin type Nb3Sn strands were tested up to an applied bending strain of 1.25% on the strand surface. Both type of samples exhibited consistent critical current degradations over the entire bending range. No discrepancies were found between the low and high bending range sample holders. The Nb3Sn samples tested all experienced a reduction in critical current between 40% and 60% at the maximum bending strain of 1.25%. The internal-tin samples experienced filament breakage and saw a permanent 30% reduction in critical current upon removal of bending. The critical current of the bronze-route samples was completely recoverable and returned to its initial critical current value upon removal of the bending strain. The experimental results of the critical current as a function of applied pure bending were evaluated with an existing integrated model. The behavior of the samples was characterized and found to be on par with previous findings for internal-tin and bronze-route wire.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Luisa Chiesa.; Committee: Makoto Takayasu, and Gary Leisk.; Keyword: Mechanical engineering.